Researching the Transition to High School for Adolescents with a Disability: Qualitative Action-Project Method as an Exemplar Approach. Issue 4 (4th July 2019) - Marshall, Sheila; Goessling, Kristen; Young, Richard; Wozniak-Molnar, Agnieszka
ABSTRACT: The transition from elementary to middle or high school is an important experience common to most adolescents in North America. However, very little research has been conducted to understand the experiences of students with a disability status and the stakeholders involved in the transition. Clearly, there is a need to generate information that views the transition as a process between students and stakeholders that takes place over time. This investigation illustrates the utility of the action-project method for studying the transition to middle or high school. Three cases involving Canadian adolescents with different disabilities (learning, sensory/motor and emotional/behavioural) and their parents, as key stakeholders, are presented.